PELATIHAN PERANCANGAN MODUL AJAR PROJECT BASED LEARNING BERLATAR BUDAYA CULTURALLY RESPONSIVE TEACHING (CRT) BAGI GURU - GURU SMPN 8 BANJAR - Kurniawan, Dian; Madawistama, Sri Tirto; Heryani, Yeni; Nurjamil, Dedi; Natalliasari, Ike (Sahira Publishing, 2024)
The formation of students' character and self-confidence based on noble cultural values ​​can be formed from the education and culture around students. Culturally responsive teaching makes people aware of respecting and recognizing the reality of different tribes, religions, languages ​​and ethnicities, and exploring the special aspects or uniqueness of students' culture and using them in planning and implementing learning. Development efforts are still very necessary, because: 1) Education is not enough to develop teacher professionalism. Many teachers take distance education/study outside the city. 2) Community Service Activities as an effort to organize education. 3) Cultural fusion as a border area. 4) Learning with a cultural background so that it can be introduced in learning. The solutions to partner problems that are addressed are: 1) The mixing of Javanese and Sundanese cultures as areas on the border is no longer considered a problem with the existence of acculturation (mixing of cultures) through the marriage process which has been carried out for a long time and produces Javanese and Sundanese descendants 2) Cultural conflict is not an obstacle because cultural acculturation has occurred in various activity sectors including religious and school activities using the language of instruction in both regions, so that it can be accepted by both parties in its delivery. 3) Community Service Activities are expected to be an implementation that can minimize inequality in technological progress and cultural inequality. 4) Culturally Responsive Teaching in daily learning is introduced by teachers through the Project Based Learning teaching module.